Chronoamperometric flow-cell designed to be unaffected by air bubbles - de Oliveira, Luiz Henrique; Trindade, Magno Aparecido Gonçalves [UNESP]; Angnes, Lucio (Elsevier, 2025)
In this paper, we present a new design for a chronoamperometric flow cell in which air bubbles do not interfere with the control of potential between the working and reference electrodes. The flow-through dual-detection cell consists of two independent parts: an upper compartment containing a quiescent supporting electrolyte solution and a channel that operates under hydrodynamically controlled conditions. In this system, the working and counter electrodes can be placed directly in contact with both compartments, whereas the reference electrode can be assembled to be either isolated or in contact with the flowing stream channel. The design ensures that the potential applied to the working electrode (controlled in the upper compartment) is similar to the potential applied in the flowing channel. The performance of the proposed flow cell in generating accurate results, even in the presence of air bubbles, was evaluated through successive air-analyte-air injections. In both series where the analyte was introduced, suitable reproducibility was achieved. The robustness of the design was definitively proven by performing a series of measurements in analytical applications for the determination of hydrogen peroxide in antiseptic samples, yielding very satisfactory results.
Keywords: Dual-detection flow-cell; Flow-through electroanalysis; Flow-through electrodes; Hydrodynamic method; Indirect controlled potential